Anti-VEGF intervention in neovascular AMD: benefits and risks restated as natural frequencies. Issue 1 (14th June 2019) - Clearkin, Louis; Ramasamy, Balasubramanian; Wason, James; Tiew, Stephenie
Abstract : Objective: Clear information is essential to properly determine preference in medical intervention. In neovascular age-related macular degeneration, patients need to understand the balance of risk and benefit of anti-vascular endothelial growth factor (VEGF) treatment. This balance is altered by the number of injections administered. Methods: Natural frequencies, displayed as pictographically as icon arrays, are used to show material outcomes from the MARINA and HARBOR (12 months) trials. We also calculated the number needed to treat (NNT) and number needed to harm (NNH). Results: MARINA 24-month data show the absolute risk reduction is 37% and the NNT is 3; meaning for one patient to benefit three need to be treated. 12 months' HARBOR data show that compared with as-needed treatment, scheduled monthly injection treatment increases the number of patients achieving a better visual outcome. The number of patients suffering harm is also increased by the additional injections. Conclusion: Displaying MARINA and HARBOR trial data as natural frequencies, with numbers needed to treat and harm, communicates complimentary information on the positive and negative aspects of anti-VEGF treatment.